Jarmo Jääskeläinen – „imigrant z polską duszą” - Hučková, Jadwiga (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
Polish topics occupy an important place in the work of the Finnish filmmaker Jarmo Jääskeläinen. Since the 70s he made his films outside censorship, and his penetrating gaze on the Polish reality allowed glimpse its dimensions closely invisible or ignored. While maintaining fidelity to the facts, he talks about the most important problems, stages the phenomena of contemporary Polish history, society, culture.